2020
DOI: 10.3390/en14010157
|View full text |Cite
|
Sign up to set email alerts
|

Optimization of the Urea Injection Angle and Direction: Maximizing the Uniformity Index of a Selective Catalytic Reduction System

Abstract: The uniformity of ammonia is very crucial for reducing the NOX emissions in a selective catalytic reduction system since the uniformity highly affects the chemical reaction between the ammonia and NOX emission. However, increasing ammonia uniformity in a short time period while injecting a urea solution is not a trivial task. Therefore, in this study, the uniformity of various urea injector designs is compared and an optimal design for the urea injector angle and direction is selected. The uniformity index (UI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
0
3
0
Order By: Relevance
“…This shows that the design parameters (D, E, and F) related to the mixer have significant contributions in improving the performance of the SCR system. The improvement of UI performance due to the optimization of the structural design parameters can also be confirmed by the experimental analysis carried out by Wardana et al [5] and Jeong et al [8]. Therefore, if optimization is focused on the design parameters of the mixer, it is estimated to be effective in reducing time and cost.…”
Section: Optimization With the Metamodelmentioning
confidence: 79%
See 1 more Smart Citation
“…This shows that the design parameters (D, E, and F) related to the mixer have significant contributions in improving the performance of the SCR system. The improvement of UI performance due to the optimization of the structural design parameters can also be confirmed by the experimental analysis carried out by Wardana et al [5] and Jeong et al [8]. Therefore, if optimization is focused on the design parameters of the mixer, it is estimated to be effective in reducing time and cost.…”
Section: Optimization With the Metamodelmentioning
confidence: 79%
“…Furthermore, there are many studies to improve UI performance. When the injection angle of ammonia is arranged in the direction of the exhaust gas flow, it improves the UI performance by 16% from the initial model [8]. The mixer equipped in the exhaust pipe causes a vortex that not only performs effective mixing of the exhaust gas and ammonia but also delays wall wetting, making a vigorous hydrolysis and thermolysis environment.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, thermal imaging indicated an exothermic character of the process through the significant release of heat on the surface where solidification occurred. Other researchers [ 7 , 8 , 9 , 10 , 11 ], have studied methods to prevent crystallization with constructive techniques such as gas mixed with AdBlue solution in order to improve gas atomized liquid droplet homogenization and to increase the performance of the selective catalytic reduction (SCR) system. Several studies can be found in the literature that investigate the use of ultrasonic vibrations in catalytic reactions, with numerous applications in green energy production [ 12 , 13 , 14 , 15 , 16 ].…”
Section: Introductionmentioning
confidence: 99%